تعويض ضحايا جرائم الإبادة الجماعية ( الأنفال وحلبجة ) طبقاً لقواعد القانون الدولي العام - الجاف, جلال كريم (Journal of Legal and Political Studies, 2013)
Accordance to the modern rules of internationals law, international responsibility of the state for genocide is a "civil" responsibility and not a criminal responsibility, and the question here is: If the Iraqi state is responsible according to the rules of international law for the crimes of genocide committed by the former regime? Does the Iraqi state bear the burden of compensating the victims of these crimes? The current solutions provided by the modern rules of international law and international judicial decisions consider these crimes as peremptory norms of general international law (jus conges), and breach of these peremptory norms involves international responsibility of the state in which they have committed these crimes against the international community as a whole. On this basis , Kurdistan Regional Government and the Kurdish civil society organizations in the region and through international organizations and non-governmental organizations, demand to the United Nations, especially the Security Council, "before release Iraq from Chapter VII ", to adopt a resolution to establish a special fund in order to deduct part of the Iraqi oil import to compensate victims of genocide (Anfal and Halabja), such as what it is it for United Nations Fund for compensation to the victims of the Iraqi invasion of Kuwait in 1990.
Keywords: Civil responsibility; criminal responsibility; International Law; Genocide